RIWAYAT KELUARGA BERHUBUNGAN DENGAN DISMENORE PRIMER PADA MAHASISWI S1 REGULER FKM UI TAHUN 2022 - Triyanti, Triyanti; Aulia, Annisa (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Primary dysmenorrhea is menstrual disorder experienced by young adult women with poor level of diagnosis and treatment. The aim of this study is to determine the proportion of primary dysmenorrhea and the relationship between risk factors and the primary dysmenorrhea among Undergraduate students of Public Health Faculty, University of Indonesia (PHF UI) in 2022. The dependent variable in this study is primary dysmenorrhea. The independent variable in this study includes intake of calcium, magnesium, zinc, vitamin E, breakfast habits, physical activity, stress level, age at menarche, menstrual duration, menstrual cycle, and family history of dysmenorrhea. The research method used is quantitative with cross-sectional design. Respondents in this study are 135 undergraduate students of PHF UI class of 2018-2021 that were selected through simple random sampling technique. Data was obtained through filling out online questionnaires via google-form. Data were analyzed by univariate and bivariate (Chi-Square test). The results showed that the proportion of primary dysmenorrhea was 86.7%. Family history of primary dysmenorrhea was significantly related to the primary dysmenorrhea, p-value = 0,038; OR = 3,318, 95%CI = (1,162-9,472). Therefore, it is important to educate on the management and prevention of primary dysmenorrhea, especially for students who have a family history of dysmenorrhea.